New Reports to the Flora of Andaman and Nicobar Islands, from Mahatma Gandhi Marine National Park, South Andaman - Karthigeyan, K.; Sumathi, R.; Jayanthi, J.; Diwakar, P. G. (Indian Forester, 2011)
Eurya nitida Korth., Scurrula parasitica L. and Tristellateia australasiae A. Rich. collected from the Mahatma Gandhi Marine National Park South Andaman forms first reports to the flora of Andaman & Nicobar Islands. Descriptions, illustrations and note on their distribution are provided.